La Red de Acción de Timor Oriental y la defensa transnacional: el cabildeo interno y la presión internacional para la autodeterminación en Timor-Leste - Lundry, Chris (El Colegio de México, 2022)
Many factors contributed to the timing, in August 1999, of the referendum in Timor-Leste that led to the country’s independence; among them: Suharto’s abdication, Indonesia’s vulnerability to pressure after the East Asian economic crisis, Indonesia’s confidence that it will prevail using its usual methods of intimidation and manipulation, and, of course, the political and armed struggle of who supported and died for independence in Timor-Leste. Another element was the solidarity networks that emerged among activists from various countries who exerted internal pressure on their governments to force them to change their policy towards Indonesia. This article examines the East Timor Action Network, founded in 1991 in the United States, and its lobbying and internal pressure strategy. Building on Sikkink and Keck’s model of principle-based issue networks and their ability to exert domestic pressure for international results, this article shows how the Network successfully lobbied for change in US foreign policy toward Indonesia and contributed to the selfdetermination in Timor-Leste.